The process of budgeting the strategy of industrial complex transformation in the context of digitalisation - A. G. Boev (Вестник университета)
The article is devoted to topical issues of budget formation and optimization of industrial complexes transformation strategies in the digital economy. The study defines the content of the budgeting strategy of transformation as a system of financial, organizational and managerial procedures focused on the formation of a balanced multi-level budget strategy and the effective expenditure of its resources on measures to modernize the enterprise. The author proposes the process of budgeting the strategy for the transformation of the industrial complex, which is distinguished by the use of the program-target method and ensures the consistency of long-term goals and the financial policy of the enterprise. Further, the researcher substantiates the allocation of strategically significant expenses of production companies into a separate category of accounting and the formation of transformation strategy budgets based on them. The budget of the change strategy includes 6 types of costs: 1) reconstruction and modernization costs; 2) information and communication technology costs; 3) research and development costs; 4) technological innovation costs; 5) organizational innovation costs; 6) marketing innovation costs. The author determines the recommended amount and horizon of the strategy budget planning and also presents a 6-stage algorithm of methodical reception on the use of neural network modeling tools to optimize the budget of the strategy of changes in the industrial complex. It is possible to use the results of the study as a methodological basis for organizing the process of budgeting strategies of industrial complexes in the digital economy.